Ablasskampagnen des Spätmittelalters Luthers Thesen von 1517 im Kontext - Rehberg, Andreas (Bibliothek des Deutschen Historischen Instituts in Rom, 2017)
Martin Luther`s Theses against indulgences (1517) provided the impetus for the Reformation. This volume examines the context of this epochal moment against the backdrop of the extensive campaigns against indulgences that had roiled Church life over the previous two centuries. The essays explore theological, canonical, societal, economic, and cultural aspects of the sale of indulgences in the Late Middle Ages.